Delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) and T2 mapping at 3T MRI of the wrist: feasibility and clinical application - Rehnitz, Christoph; Klaan, Bastian; Stillfried, Falko von; Kauczor, Hans-Ulrich; Weber, Marc-André (Journal of magnetic resonance imaging, 2017)
Purpose To assess the feasibility of delayed gadolinium-enhanced magnetic resonance imaging (MRI) of cartilage (dGEMRIC) and T2 mapping for biochemical imaging of the wrist at 3T. Materials and Methods Seventeen patients with wrist pain (mean age, 41.4 ± 13.1 years) including a subgroup with chondromalacia (n = 11) and 15 healthy volunteers (26.0 ± 2.2 years) underwent dGEMRIC and T2 mapping at 3T. For dGEMRIC, the optimum time window after contrast-injection (gadopentetate dimeglumine) was defined as the plateau of the T1 curve of repeated measurements 15-90 minutes postinjection and assessed in all volunteers. Reference values of healthy-appearing cartilage from all individuals and values in areas of chondromalacia were assessed using region-of-interest analyses. Receiver-operating-characteristic analyses were applied to assess discriminatory ability between damaged and normal cartilage. Results The optimum time window was 45-90 minutes, and the 60-minute timepoint was subsequently used. In chondromalacia, dGEMRIC values were lower (551 ± 84 msec, P < 0.001), and T2 values higher (63.9 ± 17.7, P = 0.001) compared to healthy-appearing cartilage of the same patient. Areas under the curve did not significantly differ between dGEMRIC (0.91) and T2 mapping (0.99; P = 0.17). In healthy-appearing cartilage of volunteers and patients, mean dGEMRIC values were 731.3 ± 47.1 msec and 674.6 ± 72.1 msec (P = 0.01), and mean T2 values were 36.5 ± 5 msec and 41.1 ± 3.2 msec (P = 0.009), respectively. Conclusion At 3T, dGEMRIC and T2 mapping are feasible for biochemical cartilage imaging of the wrist. Both techniques allow separation and biochemical assessment of thin opposing cartilage surfaces and can distinguish between healthy and damaged cartilage. Level of Evidence: 3 J. Magn. Reson. Imaging 2017;45:381-389.
First published: 5 July 2016
Gesehen am 26.04.2018